Determinan Profitabilitas pada Bank Jabar Banten Syariah - Wawan Oktriawan; Aris Syafaat; Safitri Rahmawati (Neolectura, 2022)
The purpose of this study was to determine how the influence of musyarokah financing and murabahah financing on profitability as measured by return on assets at Bank Jabar Banten Syariah. The method in this study uses a descriptive quantitative approach with data analysis tools using multiple regression, correlation test, determination test and hypothesis testing which includes simultaneous significance test (f test) and t test. The results of this study indicate that the coefficient of determination (R2) is 0.179 or 17.9%. This figure illustrates that the percentage contribution of the influence of musyarokah financing and murabahah financing to the Return on assets variable is 17.9%. Meanwhile, the t-test results show that the significant value of the Musyarokah financing and murabahah financing variables are 0.699 and 0.960, respectively, which is greater than the limit of the significance value of 0.05. This indicates that the Musyarokah financing variable has no significant effect on profitability. Simultaneously shows that the significance value is 0.821. because the significance value of 0.0821 is greater than the limit of the significance value of 0.05, it can be concluded that simultaneously or jointly the musyarokah financing variable with murabahah financing has no significant effect on profitability.